The Role of Mediation of Psychological Safety and Voice Efficacy on the Influence of Inclusive Leadership on Vocal Behavior - Achmad Nizar; Andang Parahanti (Eduvest - Journal of Universal Studies, 2024)
PT. XYZ as a company engaged in non-bank financial services, is required to continue to innovate. To be able to bring out innovation is through the contribution of all employees. These contributions include employees carrying out vocal behaviors, namely proactive behavior that comes from themselves or initiatives, is forward-oriented, and aims to improve a certain condition. On the other hand, the bureaucratic organizational structure makes vocal behavior a challenge for companies to develop. To encourage vocal behavior, internal and external factors of employees need to be elaborated further. This study aims to explore the role of voice efficacy and psychological safety in mediating the influence of inclusive leadership on vocal behavior. The research was conducted at PT XYZ by involving 154 respondents to fill out a questionnaire. Using the Social Cognitive Theory (SCT) approach to look at the dynamics of the influence of inclusive leadership on vocal behavior mediated by psychological safety and voice efficacy, the results show that voice efficacy significantly mediates the influence of inclusive leadership on vocal behavior, while psychological safety does not mediate the influence of inclusive leadership on vocal behavior. The results of this study indicate that the factor of individual perception of one's ability to speak up (voice efficacy) needs to be a concern by leaders so that vocal behavior can appear in the organization.